Successful research projects a guide for postgraduates - Lee, Anne (London Routledge, 2020)
"Comprehensive and accessible, this guide is the perfect companion for the busy student facing their postgraduate research project. It covers the key questions, challenges and solutions including: how to organise time most effectively; how to work with colleagues; how to stay motivated and how to get the best out of a supervisor. By providing the reader with the significant theories behind ways of managing projects, identifying important goals and solving problems, Manging your Research Project provides models for good research and writing processes as well as key practical tips within each chapter"--Provided by publisher.
Becoming a research student -- A framework for analysing what you need -- Managing your project: a functional approach -- Uncovering the implicit: embracing enculturation -- Thinking like an academic: developing criticality -- Finding your own way: enabling emancipation -- Creating and maintaining relationships -- Using the framework to help your research -- How to write like an academic -- Dilemmas when you disagree with your supervisor -- Preparing for your work to be examined -- Looking to the future.
Includes bibliographical references and index.
Keywords: Academic writing -- Handbooks, manuals, etc; Report writing -- Handbooks, manuals, etc; Universities and colleges -- Graduate work; Research -- Methodology